A descriptive study of patients with inflammatory myopathies at Tygerberg Academic Hospital and a review of current classifications - Chothia, Mogamat-Yazied (Stellenbosch : Stellenbosch University, 2022)
Thesis (MMed)--Stellenbosch University, 2009.